Hubungan Paritas dengan Keberhasilan Induksi Folley-Oksitosin pada Kehamilan Postterm - Maudy Shera Syva Aulia; Suherni Suherni; Yuliasti Eka Purnamaningrum (Poltekkes Kemenkes Yogyakarta, 2017)
American College of Obstetricians and Gynecologist (ACOG)2005, confessed that the average of spontaneous birth was 12%,23.4% stood for birth induction with medical indication, while 23.8% for birth induction without any medical indication. There was arise in birth induction in District Base Hospital of Wonosari on 2015 up to 2016, from 17% to 18.5%. The success of the birth indicationin post-term pregnancies which used folley-oxcytocin was quite high (84%). One of the factors triggering the success of the inductionwas exactly the thing called parity. The purpose was to know the relation of parity and the success of folley-oxcytocin induction whichwas done toward post-term mothers in District Base Hospital of Wonosari on 2016. Sort of observational analytic research with crosssectional design. The location of the research was in District Base Hospital of Wonosari on May 4 up to 12, 2017. The population wasthe post-term pregnant women who were induced with folley-oxytocin on 2016. The sampling method used was purposive. Thenumber of appropriate samples were 130 post-term pregnant women induced with folley-oxytocin. While the hypothesis trial tookChi-Square with 0.05 signification standard as the medium. 76.9% out of 100% post-term pregnant women were successfullyinduced with folley-oxytocin. The percentage of success of multipara case was 84.62% while the nulipara one was 69.23%. p-value0.037 was gotten in the analysis of Chi-Square which meant that there was a significant connection between parity and the successof folley-oxytocin induction, PR 1.222, 95% (CI 1,008-1,481) and 0.180 contingency coefficient with only little closeness in relation.There was definitely a relation between parity and the success of folley-oxytocin induction done towards the post-term pregnanciesin District Base Hospital of Wonosari on 2016.